Normative data of outer photoreceptor layer thickness obtained by software image enhancing based on Stratus optical coherence tomography images. Issue 6 (3rd June 2008) - Christensen, U C; Kroyer, K; Thomadsen, J; Jorgensen, T M; la Cour, M; Sander, B
Abstract : Aim: To present normative data of outer photoreceptor layer thickness obtained by a new semiautomatic image analysis algorithm operating on contrast-enhanced optical coherence tomography (OCT) images. Methods: Eight Stratus OCT3 scans from identical retinal locations from 25 normal eyes were registered and combined to form a contrast-enhanced average image. Utilising the vertical intensity gradients of the enhanced OCT images to demarcate retinal layers, thickness measurements of the outer photoreceptor- and retinal pigment epithelium layer (RPE-OScomplex ) were obtained. Additionally backscattered light within the outer nuclear layer (ONL) in the fovea was registered and compared with backscattered light within the ONL in the peripheral part of the macula (Iratio -ONL). Results: The mean RPE-OScomplex thickness in the foveal centre was 77.2 μm (SD = 3.95). The RPE-OScomplex thickness in the superior macula 0.5–3 mm of the centre was significantly increased as compared with the corresponding inferior retina. In healthy subjects, the Iratio -ONL was 1.06. Conclusions: Contrast-enhanced OCT images enable quantification of outer photoreceptor layer thickness, and normative values may help understanding better the relationship between functional outcome and photoreceptor morphology in retinal diseases.